IbM PELATIHAN DUTA KESEHATAN REPRODUKSI MANDIRI - Fitria Siswi Utami; Enny Fitriahadi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Cases of whiteness, courtship to free sex, pregnancy out of wedlock, abortion, even sexual harassment and violence are increasingly being heard. The likelihood of these problems that existed only among teenagers and adults, now turns to the age of the children. Not a few children start dating and get sexual violence by boyfriends, friends, teachers, strangers, or even by their own family. Age of childrenis the most appropriate age to instill behavior. Early reproductive health education is expected to provide a more informed associa- tion of ethics to associate with same-sex, opposite sex, and maintain personal reproductive health. This is important to be given because ignorance will lead them to try to find their own information that is often not controlled by parents. Based on Hasibuan and Sardjana(2006) research, existing reproductive health problems can be prevented through reproductive health education appropriately from an early age. In addition, the establishment of an independent reproductive health ambassador from peers with trained teacher assistance can effectively help provide information and reproductive health education to other students. The expected outcome target is the establishment of 20 independent reproductive health ambassadors in each partner school of this activity. The method of implementation will be initiated by the compilation of guidebooks on improving reproductive health, increasing knowledge and ability of cadres to help solve basic reproduction health problems that are common in elementary school age. Training activities of the Reproductive HealthAmbassadors have been implemented in each of the participating schools. Each school currently has 2 companion teachers and 20 students of self-reproductive health ambassadors. Video and module media are available as student and companion material to deliver materials to other students. Sustainabilityof reproductive health assistance activities for the future is very necessary in order to improve the quality of reproductive health. Keywords: education, reproductive health, elementary school age